2018
DOI: 10.1007/s10570-018-2163-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mechanically induced micro deformations on extensibility and strength of individual softwood pulp fibers and sheets

Abstract: Tensile tests of individual bleached kraft pulp fibers and paper sheets of industrial origin were conducted in order to investigate the effect of refining and small-scale fiber deformations on the extensibility of fibers and paper. The shape of the tensile curves of most of the fibers was concave upward (i.e., increasing slope) and consisted of two or three phases suggesting that the fibrillar structure and disordered regions in the fiber wall were straightened out during straining. Only a few of the individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
4
14
0
Order By: Relevance
“…The zero-span tensile index was usually used in characterizing the tensile strength of fibers. The results of the zero-span tensile index showed that PFI refining did not reduce fiber strength, which is consistent with the report of Kouko et al [24]. The above results showed that PFI refining improved the extent of fibrillation (especially the internal fibrillation), the swelling of fibers, and the tensile strength of sheets without a decrease of the tensile strength of fibers.…”
Section: The Morphological Analysis Swelling and Mechanical Propertiessupporting
confidence: 91%
“…The zero-span tensile index was usually used in characterizing the tensile strength of fibers. The results of the zero-span tensile index showed that PFI refining did not reduce fiber strength, which is consistent with the report of Kouko et al [24]. The above results showed that PFI refining improved the extent of fibrillation (especially the internal fibrillation), the swelling of fibers, and the tensile strength of sheets without a decrease of the tensile strength of fibers.…”
Section: The Morphological Analysis Swelling and Mechanical Propertiessupporting
confidence: 91%
“…An acid treatment was used to quantify the weak spots in fibers from kraft cooked and oxygen delignified pulps. The acid will preferentially attack the weak spots in the fibers and the chemical attack will lead to cleavage at the dislocated areas (Ander et al 2005(Ander et al , 2008Courchene et al 2002;Kouko et al 2019).…”
Section: Oxygen Delignification Influence In Fiber Dislocationsmentioning
confidence: 99%
“…Its overall objective is to achieve desired paper-making properties such as increased drainage rate of pulp, higher tensile index, burst index and density of paper, and decreased air permeability of paper [3][4][5][6]. Primarily, refining causes breakage of hydrogen bonds among the microfibrils, which subsequently increases the surface of microfibrils and the ability of fibers to establish links between them and thus the fibrillation of fibers [7,8].…”
mentioning
confidence: 99%